Exploring the complete data path for data interoperability in cyber-physical systems. (2018) - Kiourtis, Athanasios; Mavrogiorgou, Argyro; Kyriazis, Dimosthenis; Maglogiannis, Ilias; Themistocleous, Marinos
The amount of digital information increases ten-fold every year, owing to the exponential increase of cyber-physical systems (CPS), real and virtual internet-connected sources. Most researches are focused on data processing and inter-connection fields, leading to the question concerning the interoperable utilisation of data: if data is efficiently processed, how can unknown data be utilised in a different nature's application? A three-step approach is presented addressing this question, where following the data-lifecycle, a known CPS dataset is firstly stored into domain-specific language, then it gets translated into domain-agnostic language, and finally, using the fitting function of an ANN, it is compared with an unknown dataset, resulting to the translation of the unknown dataset into the first dataset's domain. A scenario of that approach is provided, analysing the data interoperability challenges and needs, emerging from today's internet of everything evolution, studying the fields of data annotation, semantics, modelling, and characterisation.